Choledochoduodenostomy for calculi in the infant - Britny Keith; Ratul Bhattacharyya; Sundus Abbasi; Jamshed Zuberi (Elsevier, 2019)
We present an unusual case of common bile duct (CBD) obstruction from gallstones in a premature infant treated by common duct exploration and choledochoduodenostomy in an abdomen with a ventriculoperitoneal shunt. We present this as an alternative method of treatment when an endoscopic method is not feasible and when a common duct -tube is thought to be suboptimal. Keywords: Biliary calculi, Choledochoduodenostomy